The factor affecting the employee loyalty in tyre manufacturing industry / Zuhayra Amirah Zulkarnain - Zulkarnain, Zuhayra Amirah
Employee loyalty is an attachment of employees with the organization, organizational goals, values and objectives. This study aimed to investigate the factors affecting employee loyalty among employees of tyre manufacturing industry at Silverstone Berhad, Taiping, Perak. Variable tested in this research included employee empowerment, employee well-being, appraisal system, employee training and job satisfaction. Researchers want to know whether these independent variables will give effect the dependent variable which is employee loyalty. This research has prepared 300 sets of questionnaires to distribute to the employees of Silverstone Berhad, Taiping, Perak. The results revealed that employee empowerment, employee well-being, employee training and job satisfaction has positive significant to employee loyalty while appraisal system has negative significant to employee loyalty. The limitation of the study, significance of the study and suggestion for future research also discussed.